2008
DOI: 10.1210/me.2007-0284
|View full text |Cite
|
Sign up to set email alerts
|

Transrepression Function of the Glucocorticoid Receptor Regulates Eyelid Development and Keratinocyte Proliferation but Is Not Sufficient to Prevent Skin Chronic Inflammation

Abstract: Glucocorticoids (GCs) play a key role in skin homeostasis and stress responses acting through the GC receptor (GR), which modulates gene expression by DNA binding-dependent (transactivation) and -independent (transrepression) mechanisms. To delineate which mechanisms underlie the beneficial and adverse effects mediated by GR in epidermis and other epithelia, we have generated transgenic mice that express a mutant GR (P493R, A494S), which is defective for transactivation but retains transrepression activity, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
4
22
0
2
Order By: Relevance
“…Our previous studies reported an EOB phenotype in K5-GR and K5-GR-TR embryos that was indeed the most consistent epithelial defect found in both transgenic mouse models Donet et al, 2008). In addition, our data demonstrated that the transrepression function of the GR is sufficient to cause these epithelial anomalies (Donet et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our previous studies reported an EOB phenotype in K5-GR and K5-GR-TR embryos that was indeed the most consistent epithelial defect found in both transgenic mouse models Donet et al, 2008). In addition, our data demonstrated that the transrepression function of the GR is sufficient to cause these epithelial anomalies (Donet et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, our data demonstrated that the transrepression function of the GR is sufficient to cause these epithelial anomalies (Donet et al, 2008). It was indeed surprising to find open eyelids in GR gain-and lossof-function mouse models although, undoubtedly, it further supports a key role for this transcription factor in ocular epithelial morphogenesis.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This indicates that the GR participates in the decision between proliferation and differentiation in a cell autonomous manner [130]. In contrast to what was seen in the case of stress erythropoiesis, this role seems to be independent of the DNA binding of the GR [130,131].…”
Section: Cell Proliferation Defects In Glucocorticoid Receptor Mutantsmentioning
confidence: 89%